ChestX-Transcribe: a multimodal transformer for automated radiology report generation from chest x-rays - Singh, Prateek; Singh, Sudhakar (Frontiers in Digital Health, 2025)
Radiology departments are under increasing pressure to meet the demand for timely and accurate diagnostics, especially with chest x-rays, a key modality for pulmonary condition assessment. Producing comprehensive and accurate radiological reports is a time-consuming process prone to errors, particularly in high-volume clinical environments. Automated report generation plays a crucial role in alleviating radiologists' workload, improving diagnostic accuracy, and ensuring consistency. This paper introduces ChestX-Transcribe, a multimodal transformer model that combines the Swin Transformer for extracting high-resolution visual features with DistilGPT for generating clinically relevant, semantically rich medical reports. Trained on the Indiana University Chest x-ray dataset, ChestX-Transcribe demonstrates state-of-the-art performance across BLEU, ROUGE, and METEOR metrics, outperforming prior models in producing clinically meaningful reports. However, the reliance on the Indiana University dataset introduces potential limitations, including selection bias, as the dataset is collected from specific hospitals within the Indiana Network for Patient Care. This may result in underrepresentation of certain demographics or conditions not prevalent in those healthcare settings, potentially skewing model predictions when applied to more diverse populations or different clinical environments. Additionally, the ethical implications of handling sensitive medical data, including patient privacy and data security, are considered. Despite these challenges, ChestX-Transcribe shows promising potential for enhancing real-world radiology workflows by automating the creation of medical reports, reducing diagnostic errors, and improving efficiency. The findings highlight the transformative potential of multimodal transformers in healthcare, with future work focusing on improving model generalizability and optimizing clinical integration.